2011
DOI: 10.1007/s00394-011-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and pro-apoptotic activities of hydroxytyrosol on different tumour cells: the role of extracellular production of hydrogen peroxide

Abstract: The pro-oxidant activity of 3,4-DHPEA deeply influences its 'in vitro' chemopreventive activities. The main initiation step in the H₂O₂-producing activity is the auto-oxidation of 3,4-DHPEA by O₂ with the formation of the semiquinone, superoxide ions (O₂(-)) and 2H(+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…Indeed, the anti-proliferative activity of 3,4-DHPEA has been widely investigated in several tumour cell types. 22,23 Therefore the variability of anti-proliferative results may depend upon both the capability of cells to eliminate H 2 O 2 by specific enzymes such as catalase and glutathione peroxidase, and the effectiveness by which 3,4-DHPEA releases H 2 O 2 in different cell culture media. 14,[17][18][19][20][21] We have recently investigated the anti-proliferative action of 3,4-DHPEA in different tumour cell lines and we found that the medium used for cell culture was responsible for the different sensibility observed by various authors on different cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the anti-proliferative activity of 3,4-DHPEA has been widely investigated in several tumour cell types. 22,23 Therefore the variability of anti-proliferative results may depend upon both the capability of cells to eliminate H 2 O 2 by specific enzymes such as catalase and glutathione peroxidase, and the effectiveness by which 3,4-DHPEA releases H 2 O 2 in different cell culture media. 14,[17][18][19][20][21] We have recently investigated the anti-proliferative action of 3,4-DHPEA in different tumour cell lines and we found that the medium used for cell culture was responsible for the different sensibility observed by various authors on different cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, depending on HTyr concentrations and cell culture media, HTyr can generate H 2 O 2 in vitro [50,54]. It was indicated that the main initiation step in the H 2 O 2 -producing activity is the auto-oxidation of HTyr by O 2 , leading to the formation of semiquinone O 2 -and 2H + [54].…”
Section: Htyr-mediated Antioxidant Activity and Cancermentioning
confidence: 99%
“…Another unclear point is represented by the reachable plasma concentrations of HTyr following HTyr administration. The large difference in plasma HTyr concentrations reported in the literature is mostly correlated to the difference in the bioavailability of HTyr [54][55][56]. The administration of HTyr as olive oil ingestion, that is HTyr associated with lipids and other polyphenols, lead to the absorption of approximately 44% of the total HTyr amount [55].…”
Section: Hydroxytyrosol and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Two separate cell lines were used for each of the breast, prostate and colon cancer types, and different IC50 values were found. The fact that the abilities of different cancer cell lines to remove H2O2 accumulating in the culture medium are different from one another affects the susceptibility of the cells to the anti-proliferative effect of HT 18 . In our study, two different ovarian cancer cell lines were used.…”
Section: Discussionmentioning
confidence: 99%